When blue is larger than red: colors influence numerical cognition in synesthesia. - Cohen Kadosh, R; Sagiv, N; Linden, D; Robertson, L; Elinger, G; Henik, A (2005)
In synesthesia, certain stimuli ("inducers") may give rise to perceptual experience in additional modalities not normally associated with them ("concurrent"). For example, color-grapheme synesthetes automatically perceive achromatic numbers as colored (e.g., 7 is turquoise). Although synesthetes know when a given color matches the one evoked by a certain number, colors do not automatically give rise to any sort of number experience. The behavioral consequences of synesthesia have been documented using Stroop-like paradigms, usually using color judgments. Owing to the unidirectional nature of the synesthetic experience, little has been done to obtain performance measures that could indicate whether bidirectional cross-activation occurs in synesthesia. Here it is shown that colors do implicitly evoke numerical magnitudes in color-grapheme synesthetes, but not in nonsynesthetic participants. It is proposed that bidirectional coactivation of brain areas is responsible for the links between color and magnitude processing in color-grapheme synesthesia and that unidirectional models of synesthesia might have to be revised.